PENGARUH SENI TARI TRADISIONAL SIMALUNGUN HAROAN BOLON TERHADAP PENDIDIKAN KARAKTER ANAK DI SANGGAR MARSIALOP ARI PEMATANG PURBA - Olyvia P N Damanik; Rumiris Lumban Gaol; Anton Sitepu; Darinda Sofia Tanjung (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
This study aims to determine whether Simalungun Traditional Dance has an effect on Children's Character Education in the Marsialop Ari Purba Art Studio. The population of this study were all children aged 9-13 years at the Marsialop Ari Purba Art Studio. The sample used in this study was purposive sampling in this case the researcher used 35 children aged 9-13 years. In this study, the researcher used a quantitative survey type method where this type of research tested the results of the study using a hypothesis technique, and the hypothesis technique chosen was the t-test hypothesis.The results of this study indicate that the traditional Simalungun Tortor Haroan Bolon dance has an average tcount of 24,843 which is greater than ttable of 1,683 in the high category and character education has an average tcount of 24,843 which is greater than ttable of 1,683 in the high category. HO accepted that there was a relationship between the traditional Simalungun Tortor Haroan Bolon dance and character education for children at the Marsialop Ari Purba art studio